Methylation of the UNC5C gene and its protein expression in colorectal cancer - Jie Wu; Guangchuan Wang; Baojun He; Xuejun Chen; Yuzhi An (Tumor Biology, 2017)
UNC5C is a member of the UNC5H family of transmembrane receptors and functions as a dependence receptor. The expression of UNC5C is lost or markedly reduced in a large proportion of cancers at the messenger RNA level . However, there is little information available regarding the protein expression of UNC5C, the relationship between UNC5C protein expression and UNC5C methylation, and the correlation between patient clinical features and UNC5C protein expression in colorectal cancer. In this study, the methylation and protein expression of UNC5C were examined in 36 adenomatous polyps, 73 colorectal cancers, and 28 corresponding normal mucosa, and the correlation between the methylation, as well as protein expression status, and the clinicopathologic features was evaluated. Furthermore, the relationship between the methylation and protein expression of UNC5C, and correlation between UNC5C protein expression and overall survival were analyzed. The results showed that aberrant methylation of UNC5C was observed in colorectal cancers (78%) and adenomatous polyps (64%). The methylation-specific polymerase chain reaction results were confirmed by bisulfite sequencing of UNC5C promoter region. UNC5C methylation was significantly higher in early tumor, node, metastasis stage (I + II) of colorectal cancers. Compared with the corresponding normal tissues, protein expression of UNC5C was significantly lower in colorectal cancers (42%) and adenomatous polyps (81%). Protein expression of UNC5C was significantly higher in early tumor, node, metastasis stage (I + II) of colorectal cancers compared with advanced tumor, node, metastasis stage. Furthermore, patients with UNC5C-negative expression had a poorer prognosis than those with UNC5C-positive expression through Kaplan–Meier survival analysis ( p  = 0.038), univariate ( p  = 0.044) and multivariate analysis ( p  = 0.045). According to Spearman rank correlation analysis, UNC5C methylation and protein expression were negatively correlated ( r  = −0.461, p  < 0.001). Together, these results suggest that UNC5C methylation may be an earlier event in the development of colorectal cancer, which was negatively correlated with protein expression. UNC5C may have a critical role in the pathogenesis of colorectal cancers and be a valuable prognostic factor of colorectal cancers patients. UNC5C may be identified as an attractive therapeutic target for the treatment of colorectal cancers in the further studies.